Analisis Pesan Dakwah Dalam Tayangan Animasi Kartun Horor Pada Akun Youtube Rizky Riplay - Ati, Eltisa; Razzaq, Abdur; Hamandia, Muhammad Randicha (CV. ITTC INDONESIA, 2024)
The development of the times has brought the whole flow of life to be sophisticated and easy. Da'wah is no exception. Da'wah does not have to be interpreted as an activity of broadcasting Islam on the pulpit alone and delivered by a da'i, but can be through various kinds of modern media today. Da'wah can also be conveyed through stories of goodness and exemplary stories. In today's modern era, da'wah can be inserted in horror and mystery stories as found in some of the content on Rizky Riplay's youtube account. Therefore, the purpose of this research is to find out the da'wah messages contained in Rizky Riplay's horror cartoon animation. The method used in this research is a type of qualitative research with a descriptive approach and uses the content analysis method . The results of this study after conducting an in-depth analysis, namely the existence of da'wah messages conveyed through the horror cartoon animation, da'wah messages including containing the message of faith, sharia and morals. in addition, the film is packed with animation and interesting stories so that even though it is animated, it is suitable to be watched by teenagers to adults.